(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of school health activities in preschool educational institutions in Bac Lieu Ward, Vinh Trach Ward, and Hiep Thanh Ward, Ca Mau Province, in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted involving all 19 personnel in charge of school health services at preschool educational institutions in the study area. Data were collected using a structured interview questionnaire developed with reference to Joint Circular No. 13/2016/TTLT/BYT-BGDĐT dated May 12, 2016, issued by the Ministry of Health and the Ministry of Education and Training regarding school health services. Data were analyzed using SPSS version 20.0 software. Results: The study results indicated that only about two-thirds of preschool educational institutions fully implemented school health activities in accordance with regulations. Major limitations included a shortage of specialized health staff, inadequate facilities and essential medicines, and irregular and unsynchronized health education communication activities. Conclusion: School health services in preschool educational institutions within the study area still face several challenges. Therefore, comprehensive and coordinated solutions are required, including strengthening human resources, improving facilities, enhancing intersectoral collaboration, and reinforcing monitoring and evaluation activities to improve the effectiveness of school health services in the coming period.